Knowledge, attitudes and practice about hepatitis B infection among medical students - Bojan Joksimović; Slavenka Janković; Biljana Mijović (Биомедицинска истраживања, 2010)
Introduction: Hepatitis B is a serious disease caused by hepatitis B virus (HBV). HBV can cause lifelong infection, cirrhosis of the liver and hepatocellular carcinoma. WHO estimates that more than 2 billion persons have been infected with HBV (including 350 million chronically infected). The aim of this study was to investigate the students’ knowledge and attitudes about HBV infection at the Medical Faculty Foca. Methods: The study was conducted among 37 students of the third year, 22 of the fifth year and 18 of sixth year at the Medical Faculty in Foca from November to December 2007. The students were interviewed by the anonymous survey. Results: Most of the examined students (96.1%) know that hepatitis B virus can be passed through sexual contact. Only 17% of the students have been vaccinated against hepatitis B. The main reason for not getting vaccinated for 75.4% medical students was the unavailability of the vaccine. Almost all participants (92.2%) believe that all medical students should be vaccinated against hepatitis B. Conclusion: Our results suggest that the students’ knowledge about HBV infection is on average level. Only 17% of students have been vaccinated against hepatitis B. The main reason for that is the unavailability of the hepatitis B vaccine.
Keywords: hepatitis B virus infection; medical students; HB vaccine; KAP study